The nature of SrLn2BIVBIIIO7(Ln=La-Sm, BIV = Ti, Sn, BIII= Sc, In) with slab perovskite-like structure - Titov, Y.A.; Slobodyanik, M.S.; Chumak, V.V.; Timoshenko, M.V. (Reports of the National Academy of Sciences of Ukraine, 2020)
The areas of existence and crystallographic characteristics of phases with a two-slab structure in the Sr3–xLnxBIV 2–xBx IIIO7 (Ln = La—Tb, BIV = Sn, Ti, BIII = Sc, In). have been defined by X-ray powder diffraction and nonlinear optics methods. The continuous phase area formation with a two-slab structure in the Sr3–xLnxTi2–xScxO7 (Ln = La—Sm), Sr3–xLnxSn2–xScxO7 (Ln = La, Pr) systems and a limited (0 ≤ х ≤ 1) phase area with a two-slab structure in the Sr3–xLnxTi2–xScxO7 (Ln = La—Sm) and Sr3–xLnxSn2–xScxO7 (Ln = La, Pr) systems have been established. In other Sr3–xLnxBIV 2–xBx IIIO7 systems, a rather narrow (x value is significantly less than 1) phase area forma tion with a two-slab structure based on Sr3B2 IVO7 has been observed. The nature of the phase relations in the Sr3–xLnxTi2–xScxO7 (Ln = La—Sm), Sr3–xLnxSn2–xScxO7 (Ln = La, Pr) systems and the linear type of concentration dependences of the parameters of the unit cell phases with a two-slab struc ture indicate that the compositions of Sr2LnTiScO7 (Ln = La—Sm) and Sr2LnSnScO7 (Ln = La, Pr) phases represent a common point in a continuous series of solid solutions of the pseudobinary Sr3B2 IVO7 – SrLn2Sc2O7 (BIV = Ti, Sc) systems. The restrictions of the possibility of the substitution of strontium and titanium atoms in the Sr3–xLnxТі2–xInxO7 (Ln = La—Sm) and Sr3–xLnxSn2–xInxO7 (Ln = La, Pr) systems with the value х = 1 gives grounds for the well-reasoned assum ption that the titanatoindates Sr2LnTiInO7 (Ln = La—Sm) and stannatoindates Sr2LnSnInO7 (Ln = La, Pr) represent individual compounds with a two-slab structure. This conclusion is also confirmed by the possibility of their formation by “growing” a second layer of InO6 octahedra in a single-slab perovskite-like block of the Sr2BIVO4 compound (BIV = Ti, Sn) with LnInО3 perovskite: Sr2BIVO4 + LnInО3 = Sr2LnBIVInO7.